REFORMASI DALAM PENEGAKAN TINDAK PIDANA PAJAK DAN URGENSI PEMULIHAN KERUGIAN NEGARA DALAM RANGKA PEMBANGUNAN EKONOMI NASIONAL - Trie Rundi Hartono; Elfrida Ratnawati Gultom (Ensiklopedia of Journal, 2023)
Abstract: Efforts to increase national development, as mandated by the founder of our nation, Mr. Sukarno, is to achieve national independence through mutual cooperation. In the context of development, the source of development funds is very important, one of which is sourced from its own finances, namely taxes. Tax as a source of development increases every year. So tax law in Indonesia is constantly being updated, one of which begins with tax reform since 1983. Based on Article 43A paragraph (1) of the KUP Law, it is emphasized that the Director General of Taxes, based on information, data, reports and complaints (IDLP), has the authority to conduct preliminary evidence checks prior to conducting an investigation into criminal offenses in the field of taxation. Preliminary Evidence Examination is an Examination conducted to obtain Preliminary Evidence regarding the allegation that a Criminal Act has occurred in the Tax Sector. Meanwhile Preliminary Evidence is circumstances, actions, and/or evidence in the form of statements, writings, or objects that can provide indications of a strong allegation that a Tax Crime is being committed or has been committed by anyone that can cause losses to state revenues. Further provisions regarding Procedures for Examination of Preliminary Evidence of Criminal Acts in the Taxation Sector are regulated in the Regulation of the Minister of Finance Number 239/PMK.03/2014. Based on these provisions, the Director General of Taxes can carry out Preliminary Evidence Audit based on the IDLP relating to a Tax Period, Part of a Tax Year, or a Tax Year, whether a tax assessment has not been issued or has been issued in the event that there is an indication of a Criminal Act in the Tax Sector. Investigation is the stage of solving a criminal case after an investigation which is the initial stage of seeking whether or not a crime has occurred in an event. There has been a change in the treatment of criminal offense arrangements before the enactment of the Job Creation Law and afterward, where there has been an update that with the enactment of the Ciptaker Law, recovery of losses on state revenues can be made up to trial (before a decision) so that the opportunity is given to perpetrators of tax crimes not only until by investigation alone. Whereas with the enforcement of legal reforms (through the Tax Cluster Creation Law), state revenues will increase and taxpayers will become more compliant. This research is descriptive research, meaning research that describes certain objects and explains things related to or systematically describes the facts or characteristics of certain populations in certain fields factually and accurately. Increasingly enhanced implementation of compliance with the Tax Law as a whole with firm socialization and law enforcement. Increasing convenience for taxpayers to report in fulfilling tax obligations.Keywords: Reform, Tax Crime, Recovery of Losses.